Effect of additives on the electromechanical properties of Pb(Zr,Ti)O-3-Pb(Y2/3W1/3)O-3 ceramics - Yoon, SJ; Joshi, A; Uchino, K (AMER CERAMIC SOC, 1997)
Dielectric and piezoelectric properties of 0.02Pb(Y2/3W1/3)O-3 0.98Pb(Zr0.52Ti0.48)O-3 ceramics doped with additives (Nb2O5, La2O3, MnO2, and Fe2O3) were investigated. The grain sizes of these ceramics decreased with increasing amounts of additives. For additions of MnO2 and Fe2O3, dielectric losses decreased, while for Nb2O5 and La2O3, these values increased. The maximum values of the mechanical quality factor Q(m), were found to be 956 and 975 for additions of 0.9 wt% Fe2O3 and 0.7 wt% MnO2, respectively, but donor dopants (Nb2O3 and La2O3) did not change the values of Q(m). On the other hand, the piezoelectric constant d(33) and the electromechanical coupling factor k(p) decreased with additions of MnO2 and Fe2O3, but improved with additions of Nb2O5 and La2O3.
Keywords: TITANATE CERAMICS